THE EFFECT OF SADARI (HEALTH TRAINING OF SELF CHECKING OF BREAST G) ON KNOWLEDGE AND ATTITUDE OF STUDENTS GRADE X OF SMKN 1 GERUNG - Ria Rizki Aminah (Politeknik Medica Farma Husada Mataram, 2020)
Health training is one of the efforts to affect other people which aimed to increase knowledge. Theone of the efforts to improve the health of women is by providing training such as SADARI. The knowledge of women to early detect the risk of breast cancer is positively affecting the health, behavior, and attitude of health so that professional nurses can develop the program of breast health. This research is aimed at determining the effect of SADARI (Health Training Of Self Checking Of Breast G) on the knowledge and attitude of students grade X of SMKN 1 Gerung. This research is designed to use a cross-sectional approach, the samples were 64 respondents selected through random sampling from 129/populations. The data were collected through questionnaires and analyzed with Wilcoxon Signed Rank Test. The research showed that (p-value)0.00<0.05 meaning that there is a significant effect of self-checking of the breast on the knowledge before and after the health training.(p-value) 0.00<0.05 meaning that there is a significant effect of self-checking of the breast on the attitude before and after the health training. There is the influence of breast self-examination health education on knowledge and attitudes on class X students in SMK N 1 Gerung.